Исследования эффективных методов защиты нефтегазового оборудования от солевых отложений - Мельник, Тамара Васильевна (НТУ "ХПИ", 2015)
В статье представлены современные технологии, применяемые при разработке нефтеносных пластов на нефтегазовых месторождениях, которые находятся на их конечной стадии разработки. Рассмотрены основные методы интенсификации добычи нефти, а также способы повышения нефтеотдачи пластов и усовершенствования изучаемых технологических процессов. Проведены лабораторные исследования отложений кристаллических солей в насосно-компрессорных трубах и определен их количественный состав. Предложены дальнейшие пути исследований.

It is known that each year the interest in enhanced oil recovery methods increases, and there is development of research aimed at finding evidence-based approach to the selection of the most effective technologies for the development of deposits. The contemporary technologies used in the development of oil reservoirs for oil and gas fields that are in their final stages of development are presented. The basic methods of intensification of oil, as well as ways to intensify oil recovery and improvement of the studied technological processes are discussed. The laboratory study of crystalline deposits of salts in the tubing is made, which results in determination of number of their members. Further avenues of research, which represent a set of measures aimed at determining the quality and quantity of the materials used; analysis and prediction of the rate of corrosion damage to the operating conditions; selection inhibitor compositions, foams as well as other technological solutions for the implementation of measures to restore the equipment of oil and gas wells and enhanced oil reservoirs are suggested. These methods will allow enhancing technology of oil extraction in oil and gas fields, which are on the last stage of their development.
The study of effective methods to protect oil and gas equipment from salt deposits
Keywords: пласт нефтеносный; обработка кислотная; скважина нефтегазовая; труба насосно-компрессорная; давление пластовое; oil-bearing stratum; acid treatment; tubing; reservoir pressure